Unit Root Test With One Endogenous Structural Break Evidence from Indonesian Time Series Data - Akhsyim Afandi (Universitas Islam Indonesia, 2006)
This paper examines the robustness of the ADF (Augmented Dickey-Fuller) unit root test to the presence of one structural break. The ADF test results show one variables out of six to be stationary. To check their robustness, two separate additive outlier (AO) models are employed: one allowing for one endogenously-determined break in the intercept and the other in the trend. These two tests can not reject the unit root null hypothesis for all the vari-ables. However, when an innovational outlier (IO) model, that allows for one endogenously-determined break is estimated, the null hypothesis can be rejected for 3 more series. The estimated break dates mostly correspond to the 1998 financial crisis in Indonesia.Keywords: unit root; stationarity; structural break, additive & innovational outlierJEL classification: C1; C22